Pengembangan Media Pembelajaran Audio Visual Berbasis Prezi Untuk Meningkatkan Minat Belajar Siswa - Piska Ayu Andira; Edi Ansyah; Khosi'in Khosi'in (Yayasan Darusssalam Bengkulu, 2023)
This research aims to find out the initial analysis of the development of Prezi-based audiovisual learning media in science subjects on the human excretory system, how appropriate Prezi-based learning media is, and how effective Prezi-based science learning media is. The type of research used is the Research and Development (R&D) research and development method, using the ADDIE research and development model. This research was carried out at SMPN 08 South Bengkulu, the research subject of UINFAS Bengkulu lecturers for validation of media, material and language experts, class VIII E students and two science subject teachers. This research instrument uses a questionnaire. The results of the development of Prezi-based audiovisual learning media on human excretory system material for class VIII SMP, the validation value from media experts was 96%, material experts 95% and language experts 88% in the very appropriate category. The teacher response questionnaire results were 94% in the very practical category. Meanwhile, the effectiveness test was carried out by testing students' interest in learning with the category of students being very interested with a percentage value of (21.4%), students being interested with a percentage value of (50%), students being quite interested with a percentage value of (28.6%) with the category very effective. In the development of Prezi-based audiovisual learning media, it presents lesson material on the human excretory system in an interactive manner, accompanied by more varied audio visuals and learning videos.